Review of Best Practice Guidelines on Aromatherapy for Olfactory Restoration: COVID-19 and Others - Adriana N. Wolffenb?ttel (Mary Ann Liebert, 2023)
Objective: The main objective of this study is to establish a training to restore the olfactory sensation after infection with SARS-CoV-2 virus and the sequel to the disease COVID-19, through the inhalation of a sequence of essential oils (EO), systematically. The secondary objective of this study aims at gathering in an organized way the publications on EO that have in the keywords, short running title, or objective the mucosa anti-inflammatory action, respiratory health action, immunological health action, mental and emotional health action, as well as EO that hinder the viral replication. The EO are lipophilic substances extracted from plant species; they are mainly constituted by terpenic structures that are therapeutic bioactives. Design: This best practice guide has made a brief compilation of previously published data into an easy-to-understand didactic table. Interventions: Based on the research compiled in the table, a sequence of EO for use by inhalation was organized. Results: According to the researchers mentioned in the review, the inhalation of EO resensitizes the neural pathways that allow the identification of aroma and flavor. Thus, when this pathway is damaged, the inhalation of EO can help to restore it in a few months, which the average time is 3 months, and can extend up to 8 months. Conclusions: Currently, the greatest demand for the restoration olfactory is due to the sequelae of disease COVID-19. However, EO can be used for a loss or decrease in smell or taste caused by other factors, such as psychotropic medications, chronic rhinitis and sinusitis, neurological pathologies, cancer treatments, postinfectious and posttraumatic olfactory loss, older people, and other causes.